2018
DOI: 10.1007/s00421-018-3891-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ischaemia–reperfusion cycles during ischaemic preconditioning on 2000-m rowing ergometer performance

Abstract: In conclusion, IPC does not improve the 2000-m rowing ergometer performance of trained athletes regardless of the length of ischaemia-reperfusion cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…; Turnes et al. ). Whilst it is well established that IPC induces the production of vasodilatory factors (nitric oxide, adenosine, etc.)…”
Section: Discussionmentioning
confidence: 97%
“…; Turnes et al. ). Whilst it is well established that IPC induces the production of vasodilatory factors (nitric oxide, adenosine, etc.)…”
Section: Discussionmentioning
confidence: 97%
“…For example, acute local IPC is often accompanied by near infrared spectroscopy-measured (NIRS) marked increases in total haemoglobin [tHb] which is an indicator of total blood volume ( Paradis-Deschênes et al, 2016 , 2017 ), and deoxygenated haemoglobin [HHb] which is an indicator of muscle oxygen extraction ( Paradis-Deschênes et al, 2016 , 2017 , 2020 ; Halley et al, 2018 ) in active muscle during intense exercise, although this is not always the case ( Supplementary Table S1 ). The tissue saturation index (TSI)—which represents the equilibrium between O 2 supply and consumption during exercise–has also been shown to be reduced along with concomitant reductions in oxygenated haemoglobin [O 2 Hb], further highlighting this deoxygenation response ( Turnes et al, 2018 ). It is not clear for how long after the treatment protocol that enhanced muscle perfusion and deoxygenation kinetics persist, but Cunniffe et al (2017) reported increased change in oxygenated haemoglobin [ΔO 2 Hb] in the vastus lateralis for at least 15 min after and da Mota et al (2019) found augmented deoxygenation responses when performing exercise 2 h after IPC, which suggests some latency in the effect.…”
Section: Effects Of Ipc On Central and Peripheral Cardiovascular Resp...mentioning
confidence: 99%
“…Our results showed that the number of cycles of ischemia and reperfusion ranged from 2 cycles 43 to 8 cycles 23 . Also, the duration of occlusion periods ranged from 2 min 61 to 10 min 54 . The majority of studies performed IPC on the day of the test.…”
Section: Discussionmentioning
confidence: 78%
“…Four articles found no effect of IPC on other performances. These included rugby, 51 rhythmic handgrips, 52 speed skating, 53 and rowing 54 …”
Section: Resultsmentioning
confidence: 99%